The Milwaukee Milestones: Revised Milestone Narratives to Use in the Evaluation of Pediatric Residents' Performance Across 21 Sub-competencies - Kalindi Dhekney; Alex Okun; Dawn Bragg; Michael Weisgerber (Association of American Medical Colleges, 2015)
Abstract Introduction Beginning in 2009, the Accreditation Council of Graduate Medical Education (ACGME) and the American Board of Pediatrics collaborated on the Pediatrics Milestones Project. The goal of the project was to create a standardized, performance-based approach to assessment that pediatrics residency training programs could use to report on trainees' progress within seven general professional competencies, each with numerous subcompetencies. Since 2014, programs have submitted to the ACGME lists of numerical ratings of their residents' progress along 21 of 52 total subcompetency domains. By this performance-based assessment approach, each resident's progress is rated based on assessments of where the residents' set of knowledge, skills, and attitudes lies along a continuum of milestones, or narrative descriptions, within the sub-competencies. Methods We extracted narrative descriptions from the Pediatric Milestones Project to use in monthly resident performance evaluations at our institution, as faculty members completing these assessments found the length of the narratives and educational jargon to be problematic. We shortened (by over a half) and simplified the wording within each narrative, to create what we call the Milwaukee Milestones. Results We designed a study to evaluate the validity and reliability of assessments made using these revised milestone narratives within seven of the 21 subcompetencies. High accuracy and interrater reliability were maintained when the Milwaukee Milestones were used in simulated evaluations completed by faculty members with an interest in medical education. We have since integrated the Milwaukee Milestones into our monthly evaluations of our residents. We recommend the Milwaukee Milestones to other programs interested in using shortened and simplified descriptors in their milestones-based evaluation tools. Discussion The Milwaukee Milestones fill a need by providing shorter, more simplified language to general faculty members charged with rating resident performance using the pediatric milestones rubric, while maintaining high accuracy and interrater reliability.